Dissecting the roles of endothelin,TGF-β and GM-CSF on myofibroblast differentiation by keratinocytes - Shephard, Pierre; Hinz, Boris; Smola-Hess, Sigrun; Meister, Jean-Jacques; Krieg, Thomas; Smola, Hans (Thrombosis and Haemostasis, 2004)
Myofibroblasts are specialized fibroblasts that contribute to wound healing by producing extracellular matrix and by contracting the granulation tissue.They appear in a phase of wound healing when the dermis strongly interacts with activated epidermal keratinocytes. Direct co-culture with keratinocytes upregulates TGF-β???????????activity and also induces fibroblast to differentiate into α-smooth muscle actin (αSMA)-positive myofibroblasts. TGF-βactivity alone cannot completely account for αSMA induction in these co-cultures, and here we analyze mechanical force generation, another potent inducer of myofibroblast differentiation in this model. Using deformable silicone substrates, we show that contractile activity of fibroblasts is already induced after 1-2-days of co-culture, when fibroblasts are generally αSMA negative. Endothelin-1 (ET-1), the most potent inducer of smooth muscle cell contraction, was up-regulated in co-cultures, while blocking ET-1 with the ET receptor inhibitor PD156252 inhibited contraction in these early co-cultures. In 4-5 days of co-culture, however, fibroblast contractile activity correlated with an increased expression of αSMA expression. Stimulation of fibroblast mono-cultures with ET-1 in a low serum medium did not induce αSMA expression; however, ET-1 did synergize with TGF-β. Surprisingly, GM-CSF, another mediatorstimulating myofibroblast differentiation in granulation tissue, inhibited αSMA expression in fibroblasts, costimulated with TGF-β and ET-1. GM-CSF activated NFκB, thus interfering with TGF-β signaling. Blocking TGF-β and ET-1 largely impaired αSMA induction in co-cultures at day 7 and, in combination, almost completely prevented αSMA induction. Our results dissect the roles of TGF-β and ET-1 on mechanical force generation in keratinocyte-fibroblast co-cultures, and identify GM-CSF as an inducer of myofibroblasts acting indirectly.
Keywords: Wound healing; myofibroblasts; endothelin,TGF-β; GM-CSF